Optogenetic manipulation of cardiac repolarization gradients using sub-threshold illumination - Marchal, Gerard A.; Biasci, Valentina; Loew, Leslie M.; Biggeri, Annibale; Campione, Marina; Sacconi, Leonardo (Frontiers in Physiology, 2023)
Introduction Mechanisms underlying cardiac arrhythmias are typically driven by abnormalities in cardiac conduction and/or heterogeneities in repolarization time (RT) across the heart. While conduction slowing can be caused by either electrophysiological defects or physical blockade in cardiac tissue, RT heterogeneities are mainly related to action potential (AP) prolongation or abbreviation in specific areas of the heart. Importantly, the size of the area with altered RT and the difference between the short RT and long RT (RT gradient) have been identified as critical determinators of arrhythmogenicity. However, current experimental methods for manipulating RT gradient rely on the use of ion channel inhibitors, which lack spatial and temporal specificity and are commonly only partially reversible. Therefore, the conditions facilitating sustained arrhythmia upon the presence of RT heterogeneities and/or defects in cardiac conduction remain to be elucidated. Methods We here employ an approach based on optogenetic stimulation in a low-intensity fashion (sub-threshold illumination), to selectively manipulate cardiac electrical activity in defined areas of the heart. Results As previously described, subthreshold illumination is a robust tool able to prolong action potentials (AP), decrease upstroke velocity as well as slow cardiac conduction, in a fully reversible manner. By applying a patterned sub-threshold illumination in intact mouse hearts constitutively expressing the light-gated ion channel channelrhodopsin-2 (ChR2), we optically manipulate RT gradients and cardiac conduction across the heart in a spatially selective manner. Moreover, in a proof-of-concept assessment we found that in the presence of patterned sub-threshold illumination, mouse hearts were more susceptible to arrhythmias. Hence, this optogenetic-based approach may be able to mimic conduction slowing and RT heterogeneities present in pathophysiological conditions.